Ceramics, clays, and the technological landscape of urban Sikyon : (2nd century BC-7th century AD) - Trainor, Conor Patrick (Trinity College (Dublin, Ireland). Department of Classics, 2013)
This thesis presents the results of the author's study of the ceramic fabrics of Hellenistic, Roman and Early Byzantine Sikyon. The overarching aim of this work is to explore some of the issues that a combined programme of ceramic fabric and typological analyses can tackle on an urban archaeological survey. This thesis begins by explaining what we know with certainty, that the presence of kiln-wasters indicates that a local ceramics industry once existed on the plateau of Sikyon, and forms an interpretative matrix outward from that point. The reason for such a format is rooted in simple necessity; The Sikyon Survey Project was a single site survey and therefore a standard listing of sites simply does not apply. The vast majority of pottery found at Sikyon appears in a single fabric family which means that a detailed listing and breakdown of fabric families and wares would be completely impractical. Finally a detailed typological catalogue of the ceramics recovered during the survey would be enormous and outside the scope of the present investigation, which aims to present a general picture of an industry through the interpretation of surface ceramics.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin.